Sol-gel approach to Eu3+ doped yttrium-rich borate phosphors - Choi, CH; Park, C; Pyun, CH; Kim, CH; Chae, HK (INT ACADEMIC PUBL, 2000)
Sol-gel derived yttrium excess YBO3:Eu3+ materials were scanned to study the application of red phosphors to PDPs. The alkoxide precursors were successfully prepared by stoichiometric addition of xY(OR)(3) and B(OR)(3) with 3 wt% Eu(OR)(3) (x = 1, 2, 3, 4, 5, and R = OCH2CH2OCH3), and their oxide materials were obtained by pyrolysis of the precursors in an air at 600-1200 degreesC. The excitation spectrum of Y3BO6:Eu3+ materials shows the highest intensity, and X-ray powder diffraction patterns of them indicates that Y2O3 phase is major with small amount of Y3BO6 phase.